Is a modification of the radiotherapeutic target volume necessary after resection of glioblastomas with opening of the ventricles? - Adeberg, Sebastian; Diehl, Christian; Jung, Carla Sabine; Rieken, Stefan; Combs, Stephanie; Unterberg, Andreas; Debus, Jürgen (Journal of neuro-oncology, 2016)
Extensive surgical resection of centrally localized, newly diagnosed glioblastoma can lead to opening ventricles and therefore carries a potential risk of spreading tumor cells into the cebrospinal fluid. However, whether ventricle opening consequently implies a greater frequency of distant tumor recurrence after radiation therapy—and, therefore, reduced survival—remains unknown. Therefore, is an adaption of target volumes in radiation therapy necessary to account for a potential tumor cell spread into the ventricle system? The present study assessed the resection statuses of 311 primary-glioblastoma patients who underwent radiation therapy. Overall, in 78 cases (25.1 %) the ventricle system was opened during surgical resection. This study assessed the connection between ventricle opening and progression-free survival, overall survival, and distant and multifocal recurrence. OS rates of patients that underwent gross total resection were superior to patients with subtotal resection (p = 0.002). PFS (p = 0.53) and OS (p = 0.18) did not differ due to ventricle opening during surgical resection. However, in a subsample of STR cases increased survival was observed when the ventricle system was opened (16.8 vs. 14.3 months; p = 0.03). The occurrence of distant (p = 0.75) and contralateral recurrence (p = 0.87) was not influenced by ventricle opening. Newly diagnosed glioblastoma patients whose ventricle systems were opened during microsurgical resection did not experience decreased survival or show increased likelihoods of distant and contralateral progressions following radiation therapy. In short, patients profit from surgical resections that are as extensive as reasonably possible, even if this entails ventricle opening. Thus, additional inclusion of the ventricles in the radiation therapy target volume after ventricle opening does not seem to be indicated.
Gesehen am 23.10.2019